Characterization and genomic analysis of an oceanic cyanophage infecting marine Synechococcus reveal a novel genus - Wang, Tiancong; Luo, Lin; Xiong, Yao; Wang, Chuxiao; Shao, Hongbing; Wang, Min; Guo, Cui (Frontiers in Microbiology, 2023)
Cyanophages play a crucial role in the biogeochemical cycles of aquatic ecosystems by affecting the population dynamics and community structure of cyanobacteria. In this study, a novel cyanophage, Nanhaivirus ms29, that infects Synechococcus sp. MW02 was isolated from the ocean basin in the South China Sea.It was identified as a T4-like phage using transmission electron microscopy.Phylogenetic analysis demonstrated that this cyanophage is distinct from other known T4-like cyanophage, belonging to a novel genus named Nanhaivirus within the family Kyanoviridae, according to the most recent classification proposed by the International Committee on Taxonomy of Viruses (ICTV). The genome of this novel cyanophage is composed of 178,866 bp of double-stranded DNA with a G+C content of 42.5%. It contains 217 potential open reading frames (ORFs) and 6 tRNAs. As many as 30 auxiliary metabolic genes (AMGs) were identified in the genome, which related to photosynthesis, carbon metabolism, nutrient uptake and stress tolerance, possibly reflecting a genomic adaption to the oligotrophic environment. Readmapping analysis showed that Nanhaivirus ms29 mainly distributed in temperate and tropical epipelagic waters. This study enriches of the virus gene database of cyanophages and provides valuable insights into the phylogeny of cyanophages and their interactions with their hosts.